Religiosity and its Impact on the Family Life Framework According to Imam Reza (Peace Be Upon Him) - Ayatollah Zarmohammadi (Journal of Global Pharma Technology, 2017)
Those who are familiar with religion and its evolutionary teachings endorse its extraordinary effect on individual and social life of human being; although there is difference of opinion regarding the scope of this influence. Some believe in the maximal role of religion and some believe in its minimal role, but what has been accepted by both groups is the very involvement of the religion in all human affairs. The current essay deal with human expectation of religion and at the same time discusses the influence of religiosity on the family life according to Imam Reza (peace is upon him). Moreover, it also debates the necessity of formation of family and its functions in the production and preservation of generation, providing peace, sense of integration and purity of generation and also such factors strengthening family foundation as generosity, good manner, adornment, and satisfaction of sexual instinct.Keywords: Life Framework, Religiosity.